PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBANTU MEDIA PATUNG TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 05 LONING - Komariyah Komariyah; Mila Karmila; Ervina Subekti (Universitas Negeri Medan, 2018)
Abstract: Effect of Media-assisted Talking stick Learning Model on Class V Students' Mathematics Learning Outcomes of SDN 05 Loning. This study aims to determine the effect of sculpture media-assisted talking stick learning model on the results of mathematics learning in class V students of SDN 05 Loning. This study involved all fifth grade students of Loning Elementary School 05. This type of research is quantitative with the experimental method and Pre-Experimental Designs (nondesigns) design. The form of research design used is one-group pretest-posttest design. Data on Mathematics learning outcomes, collected by the test method while the instruments used are objective tests. The collected data were analyzed using descriptive statistics and inferential statistics namely t-test. The results showed that there were differences in learning outcomes between students who were learning with a medium sculpture-assisted talking stick learning model with students learning with conventional learning models. Keywords: Model Talking stick Learning, Result of Learning Mathematics Abstrak: Pengaruh Model Pembelajaran Talking stick Berbantu Media Patung Terhadap Hasil Belajar Matematika Siswa Kelas V SDN 05 Loning. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran talking stick berbantu media patung terhadap hasil belajar Matematika siswa kelas V SDN 05 Loning. Penelitian ini melibatkan semua siswa kelas V SDN 05 Loning. Jenis penelitian ini adalah kuantitatif dengan metode eksperimen dan desain Pre-Experimental Designs (nondesigns). Bentuk desain penelitian yang digunakan adalah one-group pretestposttest design. Data hasil belajar Matematika, dikumpulkan dengan metode tes sedangkan instrumen yang digunakan berupa tes objektif. Data yang terkumpul dianalisis dengan menggunakan statistik deskriptif dan statistik inferensial yaitu ujit. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar antara siswa yang belajar dengan model pembelajaran talking stick berbantu media patung dengan siswa yang belajar dengan model pembelajaran konvensional. Kata Kunci : Model Talking stick, Hasil Belajar Matematika